FASCISM IN GLUKHOVSKY’S METRO 2033, METRO 2034, AND METRO 2035 - Wijaya, Sandhy Yudhystyra; Rahayu, Anik Cahyaning (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This research explores the representation of fascism in Dmitry Glukhovsky’s Metro Trilogy, that includes Metro 2033, Metro 2034, and Metro 2035. Through the lens of William Ebenstein’s seven principles of fascism, the study aims to analyze how fascist ideology is portrayed and how it impacts society within the fictional dystopian world of Moscow’s underground metro system. The research uses a descriptive qualitative method with a Marxist literary criticism approach. The data are collected from narration, character dialogue, and plot development across the novels, focusing on two prominent factions that reflect fascist elements: The Fourth Reich and The Spartan Order. The analysis applies Ebenstein’s principles, including Distrust of Reason, Denial of Basic Human Equality, Code of Behavior Based on Lies and Violence, Government by Elite, Totalitarianism, Racialism and Imperialism, and Opposition to International Law and Order. The findings indicate that fascism is portrayed through the actions, structure, and ideology of certain factions, especially the Fourth Reich, which mirrors Neo-Nazi ideologies. The Spartan Order also exhibits fascist tendencies in its authoritarian behavior. Fascism is shown to thrive in post-apocalyptic conditions where fear, control, and the need for order dominate. Its presence significantly affects individual characters and societal structures, often leading to violence, exclusion, and the suppression of rational thought and equality. This research concludes that Glukhovsky’s work serves not only as dystopian fiction but as a political critique of authoritarianism. By highlighting the dangers of fascist ideology in a fictional future, the Metro Trilogy reflects ongoing concerns about the resurgence of authoritarian values in real-world societies. Keywords: Dehumanize, Dystopia, Faction, Fascism, Violence